2018
DOI: 10.1172/jci.insight.99488
|View full text |Cite
|
Sign up to set email alerts
|

Engineered T cells targeting E7 mediate regression of human papillomavirus cancers in a murine model

Abstract: T cell receptor (TCR) T cell therapy is a promising cancer treatment modality. However, its successful development for epithelial cancers may depend on the identification of high-avidity TCRs directed against tumor-restricted target antigens. The human papillomavirus (HPV) E7 antigen is an attractive therapeutic target that is constitutively expressed by HPV+ cancers but not by healthy tissues. It is unknown if genetically engineered TCR T cells that target E7 can mediate regression of HPV+ cancers. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 59 publications
3
96
0
Order By: Relevance
“…Each of the TCR pairing strategies listed above need not be used in isolation. Indeed, a TCR construct which incorporates all three classes of modifications (murinization, additional cysteine residue, TM hydrophobicity) has recently entered a first in human clinical trial (NCT02858310) . While in principle concerns regarding TCR chain mispairing may be mitigated by condensing the structure of the TCR heterodimer into a scTCR format, no scTCR constructs have been clinically tested.…”
Section: Engineering Exogenous Tcrs To Enhance Safety Function Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Each of the TCR pairing strategies listed above need not be used in isolation. Indeed, a TCR construct which incorporates all three classes of modifications (murinization, additional cysteine residue, TM hydrophobicity) has recently entered a first in human clinical trial (NCT02858310) . While in principle concerns regarding TCR chain mispairing may be mitigated by condensing the structure of the TCR heterodimer into a scTCR format, no scTCR constructs have been clinically tested.…”
Section: Engineering Exogenous Tcrs To Enhance Safety Function Andmentioning
confidence: 99%
“…Detailed analyses from both trials revealed that the affinity‐enhanced TCRs exhibited unanticipated cross‐reactivity to antigens expressed in critical normal tissues . Consequently, testing for potential cross‐reactivity is now routinely performed during the pre‐clinical development of novel TCRs . It is important to note, however, that development of off‐tumor/off‐target toxicities is by no means a universal property of all affinity‐enhanced TCRs.…”
Section: Engineering Exogenous Tcrs To Enhance Safety Function Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporation of hydrophobic residues at evolutionary-permissive positions resulted in an enhanced surface expression of the TCR chains, leading to an improved cellular avidity and anti-tumor TCR activity [66]. Since then, this approach was successfully applied to a number of TCRs [8,[67][68][69][70].…”
Section: Isolation and Structural Modifications Of Tcrsmentioning
confidence: 99%